(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2025)
Background: Management of recurrent missed abortion is very crucial. Objective: The aim of this study was to explore the outcome of combined treatment of low dose aspirin with low molecular weight heparin (LMWH) in recurrent missed abortion cases. Methodology: This non-randomized clinical trial was performed in the Department of Obstetrics & Gynaecology at Mugda Medical College Hospital, Dhaka, Bangladesh between January 2018 and December 2019. The samples were collected from Central Police Hospital, Dhaka, Bangladesh and in a private hospital in Dhaka city. The patients who were able to give clear history of missed abortion, who had no endocrine and hypertensive disorders and who conceived spontaneously or after fertility treatment were selected as study population. After positive pregnancy test all patients started taking oral progesterone (Allylstrenol 5 mg TDS), folic acid and aspirin 75 mg daily. Patients were advised to come for ultrasonography at 6 weeks of pregnancy. After confirming intrauterine viable pregnancy by ultrasonography we started injection enoxaparin (LMWH) 40 mg subcutaneous daily to all patients and continued till 34 completed weeks. The primary end point was the live birth rate and secondary end points were the side effects, late pregnancy complications and neonatal outcome in the study population. Results: Fifteen (50.4%) patients had antiphospholipid syndrome. Among them antiphospholipid subgroup antibody found in 40.4% cases, ACLA found in 27.5% cases, LA found in 18.3% cases and both ACLA and LA found in 13.8% cases. Antinuclear antibody was positive in 10% cases. No abnormality was identified in 40.1% cases. Pregnancy continued successfully in 97.0% cases. There were no maternal and foetal complications. Except failed cases there was no need to discontinue the treatment. Conclusion: In conclusion it has found a satisfactory outcome with low dose heparin therapy. Large, well-designed randomized trials are needed to establish the heparin therapy in recurrent missed abortion. Journal of National Institute of Neurosciences Bangladesh, January 2024;10(1):57-63